Comparison of reproductive performance of Gembrong goats and male Boerka goats - Husnurrizal, Husnurrizal; Akbar, Daffa Gustia Putra; Siregar, Tongku Nizwan; Hafizuddin, Hafizuddin; Wahyuni, Sri; Anwar, Anwar; Febretrisiana, Arie (Livestock and Animal Research, 2023)
Objective: This study aims to compare the reproductive performance of Boerka goats and Gembrong goats.Methods: The research was conducted at the Sei Putih Slaughter Goat Research Workshop in Deli Serdang, North Sumatra. In this study, male Boerka (n=3) and Gembrong (n=3) goats, aged 3 years and having the same average Body Condition Score (BCS) of 3.83±0.29, were used. Reproductive performance observed included scrotal circumference, libido score, and semen quality macroscopically (volume, color, odor, and consistency) and microscopically (concentration, motility, viability, and abnormalities). The data collected was tabulated and analyzed by t test.Results: Of all the parameters of reproductive performance examined, it is known that only the parameters of semen volume (ml) and sperm concentration (x106 cells/ml) showed a significant difference (P<0.05) between Gembrong goats vs. Boerka goats with values of 0.50±0.0 vs. 1.0±0.20 and 1.557±712 vs. 4.500±317.65, respectively, while the other parameters did not show a significant difference (P>0.05).Conclusions: It was concluded that the volume and concentration of Boerka goats were higher than Gembrong goats.